Efektivitas PBL dan Make a Match dalam Meningkatkan Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Roudlotul Jannah Azmil Azizah; Desty Dwi Rochmania (JOM, 2026)
Problem-solving ability is one of the core competencies that needs to be developed in mathematics learning at the elementary school level. However, empirical evidence regarding the relative effectiveness of the Problem-Based Learning (PBL) model and the Make a Match model in enhancing this ability remains limited. This study aims to compare students’ problem-solving abilities after participating in learning activities using the PBL model and the Make a Match model on the topic of time duration comparison. This research employs a quantitative approach with an Intact Group Comparison design, involving 20 second-grade students from SDN Grogol 2 Jombang, who were divided into two treatment groups. Data were collected through an essay-based test that had been validated and demonstrated high reliability (Cronbach’s Alpha = 0.968), and were analyzed using descriptive and inferential statistics. The results indicate that the PBL group achieved an average score of 79.3, while the Make a Match group obtained an average score of 82.8. The Independent Samples T-test results show that there is no statistically significant difference between the two groups (p = 0.607). The effect size analysis also reveals a small effect (Hedges’ g = 0.224), indicating that the practical difference between the two instructional models is relatively limited. These findings suggest that both PBL and Make a Match have the potential to support the development of mathematical problem-solving skills through active student engagement in the learning process. Theoretically, the results indicate that student-centered learning characteristics and active interaction may have a greater influence on the development of problem-solving abilities than differences in the instructional models used. Nevertheless, these findings should be interpreted with caution due to the relatively small sample size and the fact that the study was conducted in a single school context.